Empowerment of Farmers and Residents in Silage, Concentrate and Complete Feed Processing Technology - Asri Nurul Huda; Sri Wardhani; Anna Safitri; Layta Dinira; Sayyid Izzudin Gatrananda; Miftahudin Arief (Universitas Pendidikan Ganesha, 2025)
Low knowledge and skills of farmers and residents in processing animal feed efficiently and sustainably. Although the potential for local raw materials is quite abundant, many farmers still rely on conventional methods that are less effective, which has an impact on the quality and availability of animal feed, especially in the lean season. Lack of access to appropriate technology and ongoing assistance are also major obstacles to increasing the productivity of the community livestock sector. The purpose of this study was to identify and formulate effective empowerment strategies for farmers and residents in developing and applying silage, concentrate, and complete feed processing technology. The type of research used is participatory action research (PAR) combined with field experimental research. The methods used include social approaches, training, and intensive assistance to target groups. The population in this study were farmers and residents involved in livestock activities, especially ruminant livestock. Data analysis is a qualitative analysis carried out for data from interviews, observations, and documentation using thematic analysis techniques or the Miles & Huberman model. The results of the activity showed an increase in farmers' skills in processing feed independently. The implications of this activity are increased livestock productivity, feed cost efficiency, and optimal utilization of local resources while reducing dependence on commercial feed.